PENGARUH PERSISTENSI LABA, STRUKTUR MODAL, KOMITE AUDIT INDEPENDEN DAN KOMISARIS INDEPENDEN TERHADAP KUALITAS LABA - Yuli Haryati; Pelinta Tarigan; Nawang Kalbuana (Pascasarjana Universitas Sultan Ageng Tirtayas, 2025)
This study aims to determine the effect of earnings persistence, capital structure, independent audit committee and independent commissioners on earnings quality in consumer goods industry sector companies listed on the Indonesia Stock Exchange for the period 2018-2022. The method applied in this study uses an associative approach that is integrated with a quantitative approach. The data source in this study comes from secondary data. The sampling technique used was purposive sampling technique using a research population of 126 companies and a sample of 35 companies. This study uses multiple linear regression as an analytical tool. Data analysis was carried out using SPSS version 25 software. Based on the results of hypothesis testing, it can be concluded that simultaneously earnings persistence, capital structure, independent audit committee and independent commissioners affect earnings quality. Partial tests of the four hypotheses proposed show that earnings persistence and capital structure have a negative effect on earnings quality, independent audit committees have a positive effect on earnings quality. Meanwhile, independent commissioners have no significant impact on earnings quality.